2014
DOI: 10.3109/08958378.2014.881940
|View full text |Cite
|
Sign up to set email alerts
|

Perlite toxicology and epidemiology – a review

Abstract: Perlite is a generic name for an amorphous volcanic alumina–silicate rock that expands by a factor of 4–20 when rapidly heated to 1400–1800 °F (760–980 °C). Both the ore and the expanded product have extensive and widespread commercial applications. Limited data on the toxicology of perlite in animal studies indicate that the LD50 (oral ingestion) is more than 10 g/kg and, from a chronic inhalation study in guinea pigs and rats, that the NOAEL for the inhalation pathway is 226 mg/m3. Health surveillance studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 35 publications
0
46
0
1
Order By: Relevance
“…As far as the environmental aspects and health issues are concerned, wollastonite is known to be a non-toxic mineral that is not hazardous to humans or wildlife, unlike other mineral insoluble dusts like perlite that was reported to entail risks (Maxim et al 2014a). In fact, a review of the available epidemiological studies on wollastonite provides no evidence to suggest that wollastonite presents a health hazard; earlier studies on workers exposed to wollastonite dust indicated a need for further study of the health hazards to be carried out to come to a final conclusion (Huuskonen et al 1983;Maxim and McConnell 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As far as the environmental aspects and health issues are concerned, wollastonite is known to be a non-toxic mineral that is not hazardous to humans or wildlife, unlike other mineral insoluble dusts like perlite that was reported to entail risks (Maxim et al 2014a). In fact, a review of the available epidemiological studies on wollastonite provides no evidence to suggest that wollastonite presents a health hazard; earlier studies on workers exposed to wollastonite dust indicated a need for further study of the health hazards to be carried out to come to a final conclusion (Huuskonen et al 1983;Maxim and McConnell 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has minimal effects on humans or wildlife, although long term exposure studies have not yet been performed (Huuskonen et al 1983, Maxim & McConnell 2005, Maxim et al 2014a. Wollastonite has a high thermal conductivity coefficient that could accelerate the transfer of heat from hot-press plates and facilitate resin curing in the center of the mat (Taghiyari et al 2013b(Taghiyari et al , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cooper and Sargent (1986) indicated that perlite dust does not pose a significant health risk for workers. However, more recent studies, such as those conducted by Maisanaba et al (2015); Maxim et al (2014); Sampatakakis et al (2013), suggest that excess of exposure to perlite dust without the necessary protective equipment might result in adverse health effects. In addition, they indicate that the potential impact of the other minerals that are present in the perlite ore should not be underestimated.…”
Section: Environmental Risks Associated With Perlite Oresmentioning
confidence: 99%
“…Authorities such as the USEPA (1995) and USPC (2012) describe the fine particles generated during mineral processing and the content of metals in the ore as potential environmental risks and therefore are considered as cost penalties, which must be below certain thresholds. The fine particles are generally treated as nuisance dust; what is more, evidence provided by Elmes (1987) and Maxim et al (2014) suggests that in large amounts, these particles represent a factor of air pollution and a potential health risk for workers. Regarding the chemical purity, even though perlite is deemed to be an inert material, it has been mentioned before that the chemical composition of the ore can still be altered by the particular geological features of the deposit, which might result in an enrichment of elements that ultimately contaminate the ore.…”
Section: Introductionmentioning
confidence: 99%